Circulating Neurofilament Light Predicts Cognitive Decline in Patients With Post-stroke Subjective Cognitive Impairment - Wang, Jian-Hong; Huang, Jie; Guo, Fu-Qiang; Wang, Fang; Yang, Shu; Yu, Neng-Wei; Zheng, Bo; Wang, Jian (Frontiers in Aging Neuroscience, 2021)
Background Subjective cognitive impairment (SCI) is common after acute ischemic stroke (AIS) and adversely affect quality of life. SCI is associated with an increased risk of developing mild cognitive impairment and dementia. Identifying biomarkers which could predict long-term cognitive outcomes of post-stroke SCI is of importance for early intervention. This study aims to investigate the association between circulating neurofilament light (NfL) and long-term cognitive function in patients with post-stroke SCI. Methods This longitudinal study recruited 304 patients with post-stroke SCI and serum NfL levels were determined at baseline. These patients were followed up for 12 months for the observation of cognitive change. Cognitive performances were assessed by a Chinese version of the Telephone Interview of Cognitive Status-40 (TICS-40) scale. Results Patients were divided into a progression group (as determined by decreased TICS-40 scores) and a stable group (as determined by increased or unchanged TICS-40 scores). The progression group had significantly higher serum NfL levels than the stable group at baseline. Serum NfL levels were predictive for a longitudinal cognitive decline during follow-up. Conclusions These findings imply that circulating NfL could predict the long-term cognitive change of patients with post-stroke SCI.